กลยุทธ์การพัฒนาส่วนผสมทางการตลาดผลิตภัณฑ์ชุมชนประเภทอาหารขบเคี้ยวของกลุ่มผู้ประกอบการในอำเภอเมือง จังหวัดแม่ฮ่องสอน - อ่อนวงศ์, ปวิช; คำไทย, วริยาวรรณ; ใจรักษ์, เสาวณี (Ganesha Journal, 2012)
[บทคัดย่อภาษาไทยไม่สมบูรณ์] This research aimed to study the enhancement of a marketing mix strategy for local snack products produced by the provincial entrepreneurs in Amphoe Muang, Mae Hong Son province. It was to study the purchase behavior characteristics of consumers buying the local snack products, and to enhance the marketing mix strategy of the products. The investigation was conducted by collecting data from the focus group discussion interview form answered by 11 entrepreneurs and from the Taro Yamane’s table answered in 400 instances at which the local snacks were consumed. The data from the entrepreneurs showed that, Producing, there was an enhancement of production lines to be new, up-to-date, and prominent. Packaging, the products were packed into various packages – boxes and envelopes, which were intended to secure the nutrients and for the safety of consumers. Pricing, the price was set by the entrepreneurs reasonable income affordable. Distributing, the products were distributed to local product centers, wholesalers, retail stores, and product exhibitions being stage by the government. Promoting, the same brand was used for all products. The data from the consumers showed the characteristics of the responders that most of them were government officers/state enterprise employees who earned 10,001-15,000 Baht a month. They purchased the snacks made from sesame for less than 500 Baht each time as souvenirs and for their own consumption. Moreover, they bought the products from attractions and general stores after considering convenient locations and various kinds of goods on shelves as they perceived the information from friends and relatives. Also, they considered the quality and convenient location as important. From the study of their purchase behavior it was found that the decision buying local snacks relied highly on an overview of the products in terms of good taste, nutritional value, shape of packaging and brand. Furthermore, the overview of pricing had affected the decision moderately. When the pricing was considered in detail, the responders gave an importance to the reasonable price as priority. Distributing, they considered the convenient location of a store was close to the main road, there were various snack products on shelves, and the purpose of the store was only for the sale of snacks.